God with us and without us volumes one and two: the beauty and power of oneness in Trinity versus Absolute Oneness - SHEHADEH, Imad. N (Carlisle Langham Global Library, 2020)
God as Trinity is at the core of the mystery and otherness of the divine nature of God. It has also been a frequent barrier to those who hold to the Absolute Oneness of God. In this combined work Dr Imad Shehadeh demonstrates the inevitability of the Trinity by exposing the conflict that Absolute Oneness faced historically. Dr Shehadeh presents the beautiful logic of the Trinity and explains how the display of God's attributes in creation derives from the self-sustaining relationships in his triune nature as Father, Spirit and Son. The book climaxes in revealing the transforming power of the Trinity when applied to life.
Includes bibliographical references and index.
Keywords: Trinity, Simplicity, Antitrinitarianism, Holy Spirit